Локальна правотворчість в механізмі правового регулювання суспільних відносин - Форманюк, Валентин Васильович (My University, 2010)
Статья посвящена отдельным вопросам локального правотворчества. Автор обосновывает свое видение изменения правовой природы локального правотворчества в зависимости от изменения функциональной направленности правовой активности.

The article is dedicated to separate questions local lawmaking. The author motivates his vision of the change the legal nature local lawmaking, depending on change the functional directivity to legal activity. In article on base of the complex study of the scientiﬁ c literature by author gives the answer to question is local lawmaking independent element lawmaking to activities or it inherent only to side realize legal phenomenon.
Keywords: локальна правотворчість; правове регулювання; суспільні відносини; правотворча активність; правова активність; правовий феномен; локальное правотворчество; правовое регулирование; общественный отношения; правотворческая активность; правовая активность; правовой феномен; local law-making; legal regulation; public relations; lawmaking activity; legal Activity; legal phenomenon